Características clínicas de la enfermedad renal crónica por uropatía obstructiva en pacientes adultos - Contreras Torres, Jorge Jhonathan (2017)
Objective: To determine the clinical and epidemiological features of chronic renal disease by obstructive uropathy in adult patients. Material and method: the population was constituted by clinical histories of 380 adult patients who were hospitalized with a diagnosis of chronic kidney disease (ICD-10N18) in internal medicine of the Hospital Belen of Trujillo services during the period 2010-2013. 346 clinical histories were excluded since they met the criteria of exclusion, being only 34 medical records of patients hospitalized with a diagnosis of chronic kidney disease with obstructive uropathy. Results and conclusions: In adult patients hospitalized for disease Renal chronic obstructive uropathy was found that the total number of cases were male, the time of disease was 3.28 years; the average age was of 71.06 6.73 ± years, the etiology of most often was benign prostatic hyperplasia with 97% and the clinical feature with highest percentage of frequency that were found were the reduction of Jet urinary (88%), urinary urgency (88%) and chronic urinary retention (65%), bilateral hydronefrosis (62%), lumbar pain (50%)